2020
DOI: 10.1093/ckj/sfaa030
|View full text |Cite
|
Sign up to set email alerts
|

Idarucizumab for the treatment of dabigatran-related nephropathy

Abstract: Anticoagulant-related nephropathy (ARN) is a clinical syndrome of acute kidney injury in patients taking vitamin K antagonists or direct oral anticoagulants. It is associated with increased mortality and there is no specific treatment. We report the case of a 78-year-old man on dabigatran who developed macroscopic haematuria and acute kidney injury 2 weeks after mitral valve repair, reaching a peak creatinine of 415 µmol/L from a normal baseline, which was successfully treated with one course of idarucizumab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…10 Interestingly, Alsamarrai et al reported a case of ARN treatment with idarucizumab, a humanized monoclonal antibody, reversing the anticoagulant effect of dabigatran. 53 Before the introduction of idarucizumab in 2015, hemodialysis was the only available specific therapy in dabigatran overload due to a low molecular weight of the drug and weak protein binding. 64 In a recently published study, Galassi et al proposed an algorithm of dabigatran overdose management in patients with eGFR lower than 30 mL/min.…”
Section: Therapeutic Approachmentioning
confidence: 99%
“…10 Interestingly, Alsamarrai et al reported a case of ARN treatment with idarucizumab, a humanized monoclonal antibody, reversing the anticoagulant effect of dabigatran. 53 Before the introduction of idarucizumab in 2015, hemodialysis was the only available specific therapy in dabigatran overload due to a low molecular weight of the drug and weak protein binding. 64 In a recently published study, Galassi et al proposed an algorithm of dabigatran overdose management in patients with eGFR lower than 30 mL/min.…”
Section: Therapeutic Approachmentioning
confidence: 99%